Allogeneic peripheral blood stem cell transplantation and accelerated atherosclerosis: An intriguing association needing targeted surveillance. Lessons from a rare case of acute anterior myocardial infarction. Issue 7 (1st October 2020) - Scudiero, Laura; Soriano, Francesco; Morici, Nuccia; Grillo, Giovanni; Belli, Oriana; Sacco, Alice; Cipriani, Manlio; Pedrotti, Patrizia; Quattrocchi, Giuseppina; Klugmann, Silvio; Oliva, Fabrizio
Abstract: We report the case of a 23-year-old man who developed an acute ST-elevation myocardial infarction secondary to acute thrombotic occlusion of the proximal left anterior descending coronary artery five years after undergoing chemotherapy, radiotherapy, haematopoietic stem cell transplantation for acute lymphoblastic leukaemia and bulky mediastinal mass involving the pleura and pericardium. His medical history also included Graft versus Host Disease developed 13 months after transplantation and acute myocarditis three months before the actual hospital admission. To the best of our knowledge, coronary artery disease as a complication of haematopoietic stem cell transplantation and low-dose mediastinal radiation therapy in young patients has been rarely reported in the medical literature. Clinicians should have a high degree of suspicion of coronary artery disease in patients treated with allogeneic haematopoietic stem cell transplantation, especially in patients previously treated with target mediastinal radiotherapy, as a group at risk of premature and significantly accelerated atherosclerosis, in order to make a timely and correct diagnosis.